Cultural Work and Higher Education
X, 271 p.
Keywords: The cultural industries are an area of continued international debate. This edited volume brings together original contributions to examine the experiences and realities of working within a number of creative sectors and address how higher education can both enable students to pursue and critically examine work in the cultural industries.